PROCRASTINATION IN COMPLETING THE THESIS - Kusuma, Aditya Tjipta; Indrawati, Endang Sri (Empati, 2013)
The purpose of this study is to describe and understand colleger academic procrastination in completing their thesis. In this study, academic procrastination in completing the thesis is generally defined as a form of deliberate delays and repeated it in completing a task or duty, either when starting or finishing thesis related to the academic field.In this study, the method used is a case study. Used two subjects and those who closest to the subject that is often interact with the subject so it can help enriching this research data. Based on the results of interviews and observations of the study, it can be concluded that the procrastination process of UNDIP Psychology colleger who was working on the thesis is influenced by several factors, internal and external. Internal factors include interpreting the subject thesis, how far the subject’s know the benefit of the thesis for them, subject’s perception toward the thesis, and subject's personality like need of achievement, need of competition, superiority, self over confidence, poor self-regulation, lack of seriousness while working on the thesis, internal conflicts occurring within the subject, perfectionist, lazy, comfortable in certain situations, external locus of control, interpersonal dependency, and the subject's ability to adapt.Meanwhile, external factors that affect procrastination process of UNDIP Psychology colleger who was working on the thesis is thesis supervisor, high expectations towards thesis supervisor and the conflict with the thesis supervisor, stressors that appears like feeling worry being blame by the thesis supervisor, and having differences of opinion with the thesis supervisor, thesis bureau or bureaucracy, a standard system that the subject feels quite high compared with other faculties and other universities, other barriers, such as lost social support, social pressure, trouble getting a thesis supervisor, difficulty in obtaining subjects, title changed many times, difficult to meet the supervisor, difficult to get a reference, and less guidance from thesis supervisor.